2005
DOI: 10.1016/j.febslet.2004.12.089
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of anticancer peptide from Mercenaria on the BGC‐823 cells and several enzymes

Abstract: An anti-cancer peptide was purified from the Mercenaria (Meretrix meretrix Linnaeus) by the method of chromatography on Sephadex G-25 and FPLC, and its molecular weight was determined to be 3147 Da by the way of MALDI-TOF mass spectrum. The effects of this peptide on human gastric gland carcinoma cells (BGC-823) and their cytoskeletal morphology were investigated. The results showed that the peptide could inhibit the proliferation of BGC-823 cells and obviously destroy the skeletal structures of the cells. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 9 publications
1
34
0
1
Order By: Relevance
“…In addition to its fatal effects on human body such as tissue degeneration, ROS may also join in generation as well as in malign transformation of cancer cells. If newer compounds from natural sources can enhance the level of antioxidation within the body and clear the ROS in cancer cells, they may inhibit the cell's growth and may thereby play a vital role to treat cancer in combination with the anticancer drugs (Lee et al, 2003;Leng et al, 2005). In our research, the ethanol extract of T. erecta was found to scavenge the DPPH free radical indicating that this property may contribute equally or enhance its cytotoxic potential.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to its fatal effects on human body such as tissue degeneration, ROS may also join in generation as well as in malign transformation of cancer cells. If newer compounds from natural sources can enhance the level of antioxidation within the body and clear the ROS in cancer cells, they may inhibit the cell's growth and may thereby play a vital role to treat cancer in combination with the anticancer drugs (Lee et al, 2003;Leng et al, 2005). In our research, the ethanol extract of T. erecta was found to scavenge the DPPH free radical indicating that this property may contribute equally or enhance its cytotoxic potential.…”
Section: Discussionmentioning
confidence: 67%
“…Several peptides and proteins derived from M. meretrix with antitumor activity have been isolated; Leng et al (2005) demonstrated a peptide extracted from M. meretrix significantly inhibited the proliferation of human gastric gland carcinoma cells by affecting activities of SOD, ALP and tyrosinase. In our previous study, two peptides have been isolated form M. meretrix, in which MML and Mere15 exhibited high anticancer activity (Ning et al, 2009;Wang et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Several peptides and proteins with antitumor activity have also been extracted from M. meretrix. Leng et al purified a peptide from M. meretrix, which exhibited strongly inhibitory effect on the growth of human stomach adenocarcinoma BGC-823 cells (18). In addition, two glycoproteins, MGP0405 (MW: 9,655 Da) and MGP0501 (MW: 15,878 Da), were reported to have anti-tumor effect in vitro (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to show that M. meretrix has anti-cancer efficacy, eliminating cysts and detoxification (15)(16)(17)(18). Several peptides and proteins with antitumor activity have also been extracted from M. meretrix.…”
Section: Introductionmentioning
confidence: 99%